(untitled) (International Seven Journal of Multidisciplinary, 2025)
This article deals with the training of the teaching professional in the face of new technologies, and the Podcast as a resource in the classroom, because technological tools, especially the computer, are fundamental to the development of teacher autonomy, especially in public schools, but many of them do not master the handling of this technology. In this context, it is perceived that it is necessary to have the professional training of teachers in the face of technologies and it is an issue of extreme relevance that must be widely discussed and made feasible so that all educators can insert themselves in the age of information technology by performing a dual role, the mediator and the conductor of learning. Because learning does not happen in isolation, it is an interaction between those involved. And to interact, knowledge is needed.